A meta-analysis of the pooled impact of CYP7A1 single nucleotide polymorphisms on serum lipid responses to statins - Lim, Megan Yu Cai; Tee, Jia Rong; Yau, Wai-Ping; Ho, Han Kiat (Frontiers in Genetics, 2023)
Background and Aims Various publications suggested that there is an association between CYP7A1 single nucleotide polymorphisms (SNP) and a reduced response to statin therapy, but the results were inconsistent. This study aimed to collectively review these publications to appraise the effect of statins on cholesterol control in carriers of CYP7A1 variant alleles. Methods PUBMED, Cochrane and EMBASE were searched systematically to identify reported studies on the lipid responses to statin treatment between carriers of the variant allele versus the non-variant allele of CYP7A1 SNPs. The change from baseline in lipid responses for all included studies were calculated using weighted mean differences (WMD) (with 95% confidence interval (CI)). A meta-analysis was conducted to pool results using either the random-effects model or the fixed effects model. Results A total of 6 publications comprising of 1686 subjects for the assessment of total cholesterol, LDL-C and HDL-C and 1156 subjects for the assessment of triglycerides were included in the meta-analyses. Subjects who were non-carriers of a CYP7A1 SNP had a greater reduction in total cholesterol (overall WMD -0.17, 95% CI -0.29, -0.06) and LDL-C levels (overall WMD -0.16, 95% CI -0.26, -0.05) as compared with subjects who borne the variant allele of CYP7A1 SNPs when administered a statin. Conclusion The presence of variant allele of CYP7A1 SNPs may result in suboptimal control of total cholesterol and LDL-C levels as compared with individuals who do not carry the variant allele, when administered an equivalent dose of statin.